Determination of Oligomycins Hydrophobicity Parameters - A. N. Danilenko; M. V. Bibikova; I. A. Spiridonova (Антибиотики и Химиотерапия)
The parameters of hydrophobicity of five oligomycins, i. e. A, B, C, F and SC-II were determined by HPLC. The location of the ascending hydrophobicity parameter was set: oligomycin B < oligomycin SC-II < oligomycin A < oligomycin F < oligomycin C.